DATAEXPLAINER: Comprehensible Agentic Data Science with Consumer-Grade Hardware - Lima, João Paulo Paiva; Pereira, Marluce Rodrigues; Pereira, Denilson Alves (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2026.249146, 2026)
Data Science (DS), a complex field often involving advanced knowledge of statistics, mathematics, and programming, has historically been restricted to deeply knowledgeable human professionals. Recent advancements in artificial reasoning and the expanding toolset of large language models (LLMs) have challenged this paradigm. However, most LLM-based approaches for automated DS are still computationally demanding, time-consuming, and not especially easy to follow. In this work, we expand on previous advancements to present DATAEXPLAINER, a framework for automated DS that provides step-by-step solutions and surpasses the average Kaggle user while using a single consumer-grade GPU and less than 2 hours of processing.